The role of education on women's empowerment: the case of Village Institutes in Turkey, 1940-1946 - Birced, Çiğdem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
By taking the case of the Village Institutes (VIs) experience in Turkey, 1940-1946 period in particular, this thesis aims to investigate and answer the question of whether VIs' education (including its tools: pedagogy, curriculum, activities, methods and the system) contribute to the empowerment process of its women graduates by challenging the pressure and the gender norms of patriarchal society? 1940-1946 was the period that the foundational aims of the VIs were implemented despite the adverse impact of patriarchal society, which reinforced private/public dichotomy, subordination of women to men and disabled female education in rural Turkey. It was, also the time when the Republican project of modernization, nation building and democratization and its focal point of women's emancipation and education were in the foreground of the political sphere. By benefiting from the models of power, empowerment theory and critical theory in education, and by applying Rowlands'(1997) qualitative model as theoretical framework, this thesis examines whether the contribution of VIs' to education was sufficient to challenge patriarchal pressure and to empower its women graduates on personal, collective and relational levels. Based on evidence from the interviews, this thesis argues that VIs' education contributed to its women graduates' personal development and empowerment in personal level. However, it was not enough by itself in challenging gender norms, patriarchal obstacles and pressure of society, which limited women graduates' collective (social) empowerment and inhibited empowerment within close relationship level.
Keywords: Rural schools -- Turkey.; Education, Rural -- Turkey.